Pengembangan Media Pembelajaran E-Learning Metode Gamification Berbasis Moodle Pada Mata Pelajaran Geografi - Anwar, Sri Wandani; Maryati, Sri; Koem, Syahrizal (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to develop e-learning media gamification methods based on moodle on subjects of geography, biosphere material in XI grade State High School 1 Kabila. The research uses the ADDIE development methodology that consists of stages analysis, design, development, implementation, and evaluation. Media validation is conducted by material experts, media experts, and geography teachers. This learning media was tested on students and student responses were collected through questionnaires. Material expert validation shows a validation score of 85%, media expert validations score 94.56%, and geography teacher validation scores 80%. The average student response to the learning media is 89.64% which indicates a positive response of the student to the developed learning media. The results of the study showed that the moodle-based gamification method is suitable for use as learning media in schools and gets a very good response from students.